1992
DOI: 10.1159/000109009
|View full text |Cite
|
Sign up to set email alerts
|

GM1 Ganglioside Therapy in Acute Ischemic Stroke

Abstract: A double-blind, randomized, placebo-controlled clinical trial, involving two Italian centers, was carried out to evaluate the efficacy and safety of the monosialoganglioside GM1 in acute ischemic stroke. A total of 112 consecutive patients were recruited. The treatment (GM1 or placebo) was intravenously administered for 3 weeks and the follow-up lasted for 6 months. Semiquantitative clinical evaluations were performed on admission at the end of treatment (day 21) and at the end of follow-up (day 180), by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, it is likely that injection‐site reactions occur more often when the intramuscular route is used. An allergic reaction was reported in one patient by Angeleri et al , 9 and one patient who received GM 1 in the EST trial 13 developed an acute ascending polyradiculopathy (Guillain‐Barré syndrome). Other isolated reports of Guillain‐Barré syndrome (GBS) have raised concerns in some European countries sufficient to result in suspension of the drug's distribution, but this concern is mitigated by the fact that after analysis, many of the anecdotal reports of GBS referred to patients who had received GM 1 after symptoms had started or there were conditions prior to use of GM 1 such as diarrhea, perhaps from Campylobacter jejuni that could have been the cause of the GBS.…”
Section: Randomized Double‐blind Placebo‐controlled Clinical Trialsmentioning
confidence: 95%
See 3 more Smart Citations
“…However, it is likely that injection‐site reactions occur more often when the intramuscular route is used. An allergic reaction was reported in one patient by Angeleri et al , 9 and one patient who received GM 1 in the EST trial 13 developed an acute ascending polyradiculopathy (Guillain‐Barré syndrome). Other isolated reports of Guillain‐Barré syndrome (GBS) have raised concerns in some European countries sufficient to result in suspension of the drug's distribution, but this concern is mitigated by the fact that after analysis, many of the anecdotal reports of GBS referred to patients who had received GM 1 after symptoms had started or there were conditions prior to use of GM 1 such as diarrhea, perhaps from Campylobacter jejuni that could have been the cause of the GBS.…”
Section: Randomized Double‐blind Placebo‐controlled Clinical Trialsmentioning
confidence: 95%
“…In order to obtain convincing evidence of efficacy, clinical trials of GM 1 in acute stroke were initiated more than a decade ago. In this paper, I have focused first on the randomized, double‐blind, placebo‐controlled trials as in the five early trials listed in Table 1: three (references 7–9) concluded that GM 1 was efficacious, whereas two (references 10 and 11) concluded that there were no significant differences between patients who were given GM 1 and those given placebo. However, one of the latter (reference 10) did show that patients who received GM 1 did slightly better than the placebo‐treated group, although the difference was not statistically significant.…”
Section: Randomized Double‐blind Placebo‐controlled Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations